2015
DOI: 10.1159/000368866
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Submucosal Dissection as Total Excisional Biopsy for Clinical T1 Colorectal Carcinoma

Abstract: Background/Aims: Only the depth of submucosal invasion can be estimated prior to determining the indications for endoscopic submucosal dissection (ESD) as a curative treatment for colorectal carcinoma (CRC). Here we evaluated the outcomes of ESD for clinical T1 CRCs. Methods: Of 660 patients who underwent ESD for CRC at the Hiroshima University Hospital between June 2003 and December 2013, we examined the outcomes of 37 (6%; 26 men, 11 women; mean age ± SD, 68 ± 12 years) who underwent ESD as total excisional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 25 publications
(37 reference statements)
0
30
1
Order By: Relevance
“…The risk factor for perforation was a prolonged procedure time, and the risk factors for postoperative bleeding were a prolonged procedure time, tumor location in the rectum, and definitive colon cancer with a pathological diagnosis. Previous studies indicated several risk factors for serious complications with the colorectal ESD including the tumor location, fibrosis of the lesion, difficult endoscopic operability, and rich vascularity (27,40,47,51,54-62) The present retrospective study did not indicate these factors to be risk factors for serious complications, so further studies may be required to assess the reasons for the discrepancies in these findings. A prolonged procedure time being recognized as a risk factor in the present study was probably due to the difficulties associated with ESD, including those based on the tumor location, fibrosis, and difficult endoscopic operability, as previously reported.…”
Section: Discussioncontrasting
confidence: 66%
“…The risk factor for perforation was a prolonged procedure time, and the risk factors for postoperative bleeding were a prolonged procedure time, tumor location in the rectum, and definitive colon cancer with a pathological diagnosis. Previous studies indicated several risk factors for serious complications with the colorectal ESD including the tumor location, fibrosis of the lesion, difficult endoscopic operability, and rich vascularity (27,40,47,51,54-62) The present retrospective study did not indicate these factors to be risk factors for serious complications, so further studies may be required to assess the reasons for the discrepancies in these findings. A prolonged procedure time being recognized as a risk factor in the present study was probably due to the difficulties associated with ESD, including those based on the tumor location, fibrosis, and difficult endoscopic operability, as previously reported.…”
Section: Discussioncontrasting
confidence: 66%
“…ESD for circumscribed dysplasia in ulcerative colitis can spare patients from unnecessary surgery. ESD can also be performed for curative purposes, as well as for diagnosis [20,21]. ESD is still a technically demanding technique compared with EMR and requires intensive training [22].…”
Section: Resultsmentioning
confidence: 99%
“…It is therefore important to consistently achieve R0 resection and provide therapy to prevent recurrence. This concept is similar to the therapeutic strategy of colorectal ESD [24]. In addition, even though EMR is technically easier to perform than ESD, ESD should be indicated when tumors are depressed lesions, which could not achieve good mucosal elevation by submucosal injection even if they are small, and when treatment conditions are poor due to, for example, poor endoscopic maneuverability.…”
Section: Discussionmentioning
confidence: 99%